2009
DOI: 10.1007/978-1-4419-1399-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-derived Factor Receptor (PEDF-R): A Plasma Membrane-linked Phospholipase with PEDF Binding Affinity

Abstract: Pigment epithelium-derived factor (PEDF), a multifunctional protein, acts in retinal differentiation, survival and maintenance by interacting with high affinity receptors on the surface of target cells. We have recently identified PEDF-R, a new member of the patatin-like phospholipase domain-containing 2 (PNPLA2) family with characteristics of a PEDF receptor. The PEDF-R sequence reveals a patatin-like phospholipase domain toward its amino-end, and four transmembrane domains interrupted by two extracellular lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
(40 reference statements)
1
39
0
Order By: Relevance
“…PEDF-R Is Critical for PEDF Retinal Survival Activity-We and others have shown that rat retinal precursor R28 cells respond to PEDF stimuli, express the Pnpla2 gene, and contain active PEDF-R protein in their membrane extracts (26,35,40,41). To determine if PEDF-R is a functional receptor for the activities of PEDF in these cells, we first corroborated the location of the PEDF-R protein to the R28 cell surface.…”
Section: Expression Of Pedf-r Fragments Fused To N-end-his 6 /Xpressmentioning
confidence: 90%
See 3 more Smart Citations
“…PEDF-R Is Critical for PEDF Retinal Survival Activity-We and others have shown that rat retinal precursor R28 cells respond to PEDF stimuli, express the Pnpla2 gene, and contain active PEDF-R protein in their membrane extracts (26,35,40,41). To determine if PEDF-R is a functional receptor for the activities of PEDF in these cells, we first corroborated the location of the PEDF-R protein to the R28 cell surface.…”
Section: Expression Of Pedf-r Fragments Fused To N-end-his 6 /Xpressmentioning
confidence: 90%
“…Indeed, PEDF-R exhibits PLA 2 , triglyceride lipase, and acylglycerol transacylase activities (26,34). Moreover, we have shown that PEDF stimulates the PLA 2 activity of the PEDF-R enzyme, resulting in the release of fatty acids from phospholipids (26,35).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…In our previous studies, we showed that endometrial cells express Patatin-like phospholipase domain-containing protein 2 (PNPLA2; ref. 22), a PEDF receptor (PEDF-R) that mediates mainly prosurvival activity (24). Another key protein that regulates the anti-angiogenic activity of PEDF is laminin receptor (LR; ref.…”
Section: Introductionmentioning
confidence: 99%